Podcast Effects on EFL Learners’ Listening Comprehension - Abdul Rahman; Haryanto Atmowardoyo; Kisman Salija (ELT Worldwide: Journal of English Language Teaching, 2018)
Undoubtedly the Internet sources are absolutely beneficial to the senior high school students since they carried the target language together in itself. The present study aimed to explore podcast effects on EFL learners’ listening comprehension. This study involved sixty students chosen from the eleventh grade students of the science department at SMU Negeri 1 luwu in 2017/2018 academic years. They divided into two groups, namely the experimental and control group. The listening comprehension test and the open-ended questions administered to fulfil the objectives of the study. The quantitative data were analysed by utilizing paired and independent samples t-test, and the qualitative data was analysed through an open coding technique by identifying, naming, and describing the phenomena of the gathered data. The quantitative results indicated that the use of podcast was more effective than the use of non-podcast. It was proven by the value of the mean score from both of the groups (53.73 ˃ 37,46). The different (df) of  those two mean scores was statistically significant based on the the t - test value at 0.05 significance level. The probability value was smaller than significant level (0.000 < 0.05). In other words, the result of hypothesis testing found that t-value = 4.791 was higher than t-table = 2.000 (p=0.05, df =58). Ha was accepted and Ho was rejected. In addition, the result of open-ended question analysis highlighted that podcast was attractive in the teaching and learning of English as a foreign language listening comprehension.Podcast, Listening Comprehension, Learning Interest